El régimen disciplinario de los abogados en libre ejercicio previsto en El Código Orgánico de la Función Judicial del Ecuador - Yanangómez Poma, Javier Ricardo (2015)
This work of legal research, I have developed in the legal field of public law, specifically the shortcomings that exist in the Organic Code of the Judicial Function of Ecuador, regarding the discipline of free exercise Attorneys. The aim of this paper is to analyze and discuss the assurance guarantee access to justice for society as an essential aspect of professional practice of law, without exclusion and labor lawyers who can act without pressure or fears; without defending the right to generate persecutions, pressures, prosecution or economic demands. The Constitution of our country is the basis of our legal system and matrix through which lawmakers made the standard, the same which in turn must be consistent with the Constitution, respect these principles and rights. In this paper, a review of the rules contained in the Organic Code of the Judiciary, for sanctions to lawyers in free practice, contradicting some constitutional and legal norms, protected by international treaties and competition exposed National Council of the Judiciary, to exercise disciplinary powers against the free exercise Attorneys; thus contributing to the legal and doctrinal analysis of this research problem, in order to arrive at a logical and consistent solution and establish best recommendations thereon, hoping to clarify certain questions that allow us to reach goals related interests our legal system. In addition, our Constitution as a principle of immediate application, states that all people are equal and enjoy the same rights, duties and opportunities, no one may be discriminated against for any distinction, personal or collective, temporary or permanent, which has the purpose or effect impairing or nullifying the recognition, enjoyment or exercise of rights. For these reasons, this investigation seeks to determine the application of the principles contained in the Constitution and international instruments in relation to the free exercise of lawyers in our country